A Clinical Review of Biosimilars Approved in Oncology. Issue 3 (March 2021) - Ngo, Dat; Chen, Jason
Objective: To summarize and review the clinical data of Food and Drug Administration (FDA)-approved biosimilars for use in treatment of cancer and the current challenges health care institutions face when implementing a newly approved biosimilar. Data Sources: A literature search of the following databases was performed between January 1, 2012, and December 31, 2019: PubMed, Google, and ClinicalTrials.gov. Search terms included the words biosimilar, bevacizumab, rituximab, and/or trastuzumab . Study Selection and Data Extraction: Only primary literature on biosimilars with an ongoing or completed phase 3 trial and/or FDA approval were included in the final analysis. Primary literature consisted of peer-reviewed publications, published abstracts, and any results posted on the ClinicalTrials.gov database. Data Synthesis: Clinical trials of FDA-approved biosimilars for bevacizumab, rituximab, and trastuzumab showed no significant differences with respect to efficacy, safety, and pharmacokinetics when compared with their reference products. Relevance to Patient Care and Clinical Practice: The anticipated growth of biologics in oncology and the recent introduction of biosimilars over the past few years have placed a lot of emphasis on biosimilars as a significant source of cost savings for the health care system. Our article compiles and analyzes existing data on biosimilar efficacy, safety, and financial impact. Conclusions: The major concerns of biosimilars revolve around their long-term efficacy and safety. Even with many questions to be answered, biosimilars have the potential for significant cost savings in the US health care system.